(untitled) (Global Journal of Management and Business Research, 2025)
Employee misconduct EM exists in every organization including law enforcement agencies Law enforcement officers such as police officers can easily abuse their power or exploit their position for personal gains which subsequently will tarnish the image of the enforcement agencies as a whole The main objective in this study is to examine the relationship between antecedents i e self-control integrity organizational justice organizational politics salary financial pressure and lifestyle stress and EM among enforcement officers in Malaysia This study also to examines the impacts of opportunity on the relationship between antecedents and EM as a moderator variable This study adopted a cross-sectional survey and the data was collected from the police officers sample n 428 in the area of Kuala Lumpur Selangor Johor Perak and Sabah This study found that self-control organizational justice salary financial pressure and stress contributes significantly to EM However integrity organizational politics and lifestyle did not contribute significantly to EM Findings also revealed that self-control organizational justice salary and financial pressure contributes significantly to stress In addition this study also supported the moderating effect of opportunity on the relationship between antecedents i e self-control integrity organizational justice and salary and EM